INDICATIONS FOR IMPLANTATION OF A PERMANENT DRIVER’S TRANSPLANTED HEART RHYTHM AND CHOICE OF A TREATMENT ELEKTROKARDIOSTIMULYATION - S. J. Shemakin; M. G. Lukava; A. J. Kormer (Вестник трансплантологии и искусственных органов, 2009)
This report presents retrospective analysis of using artificial pacemaker in 16 heart transplanted patients because of developmented bradiarithmic disfunctions in the early and later posttransplanted periods. DDDR or SSIR regimens are recommended for persistened disfuncion of sinus node. DDDR regimen is recommened to prevent atrio-ventricular conduction.